Pengaruh Self-efficacy terhadap Kecemasan Berbicara didepan Umum - Ansari, Ansari; Rusli, Devi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
This study ains to determine the of self- efficacy on public speaking anxiety. The design of this study is quantitative correlational.Tthe population in this study students majoring in psychology. Univeristas Negeri Padang. The sampling technique used was purposive sampling, with the number of samples in this study were Psychologi student in the first academic year UNP as many as 83 people. Data collection was performed using data using self-efficacy scales and public speaking anxiety scales. The analysis technique used is a sample linear regression analysis test. The results showed a significant negative effect of self-efficacy on public speaking anxiety on students. Self-efficacy affects public speaking anxiety by 60,7% and 39,3% is influenced by other variables